SEXUAL ABUSES IN THE CATHOLIC CHURCH OF INDIA: NEED OF HOLISTIC HUMAN FORMATION - Lourdhu, Jeevaraj (Asian Horizons, 2020)
Sexual abuse in the Catholic Church has become a universal phenomenon. But, the Church was silent for a long time regarding this issue. Now the silence is broken and the Catholic Church has clearly revealed its stand that it is for zero tolerance against the child sexual abuse and insists on doing justice to the victims. In the Indian scenario, sexual abuse of minors and vulnerable adults is emerging as a major concern. Due to the culture of silence in India on sexuality, we do not have sufficient data on sexual abuse of minors and vulnerable adults. However, the Catholic Bishops’ Conference of India, in order to eradicate this problem, keeps zero tolerance policy on sexual abuse. To achieve this aim, we need to have an appropriate formation in the seminaries so as to train future priests to abstain from abuses. That is why we insist on holistic formation which includes human, spiritual, intellectual and pastoral dimensions of formation. This is purely a self-formation by interiorizing the human virtues and adequate understanding of sexuality and the purpose of being a celibate for the kingdom of God. Priest should learn not to underestimate the role of laity and to take positively the constructive criticisms which are given by the lay people for the pastoral ministry. The on-going formation of priests would be a great help to attain moral and spiritual integrity.